Analysis of Subsoil Liquefaction Potential in The Region of Mataram City in Indonesia - Puspitaningrum, Intan (Syntax Literate, 2021)
One of the reasons of subsoil liquefaction are cyclical loads induced from earthquake. It generally take in the subsoil when there is a loose saturated granular soil. Loose, sand and silty sand have the highest probability of liquefaction. Most places prone to this event are the subsoil that is close to water source, namely river or bay area. Mataram city is located on the west coast of Lombok Island. It acts as the capital and economic powerhouse of the region. The 2018 M7.0 earthquake showed how devastating the earthquake effect on people’s livelihood. Understanding the potential of subsoil liquefaction to happen is crucial to help government and people on the potentially affected area to adjust the proper mitigation actions. Upon analysis of soil data taken from 9 SPT sites and 22 CPT sites, it is concluded that the subsoil of Mataram city is prone to exposed with liquefaction with the most severe area is the west coast of the city and the least probable is the eastern part. Maximum settlement is forecasted to be 0.458 m taken from CPT-21 site.